Accounting and Control of Expenditure of Labour - Mackevičius, Jonas; Mačiuitis, Juozas; Subačienė, Rasa (Ekonomika, 2006)
Expenditure of labour problem is an urgent economical problem in every country of market economy without an exception. Interests of employers and employees directly interfere when dealing with the problem. Most of the authors analyse expenditure of labour taking into consideration only about payment. But it is important to manage and control the whole range of expenditure of labour. Nevertheless, there is still no specific accounting and control system. In order to avoid corrupting of the information concerning expenditure of labour and prevent from different abuse cases and illegal actions it is suggested to divide all the expenditure of labour into 4 groups: 1) expenditure of labour payment; 2) expenditure for training; 3) social expenditure; 4) other expenditure of labour. Expenditure of labour payment making the larger part of expenditure of labour influence employee work efficiency mostly. Therefore before creating a policy for determining labour payment it is advised to consider the attitude that the employees should earn in accordance with their labour input. Expenditure of training can be described as an investment into people who can influence company work efficiency and financial results. Social expenditure consist of payment concerning disability to work, compulsory social assurance fees, different type grants, fees for the sake of employees, company health care employees expenditure of labour and other expenditure of similar nature. However social and other expenditure of labour being a part if the whole company expenditure range on the one and make favourable work conditions for an employee and on the other hand - decrease company competitiveness. Accounting of expenditure of labour is one of the most complicated finance accounting sections. All the expenditure referring to the model accounting plan are taken into accounts of class 6 “Expenditure”. Accounts 6103. “Sales persons salary and related expenditure” and 6114 “Administration salary and related expenditure” are dedicated to accounting of employee salary and related expenditure. However there are no separate accounts for expenditure of labour of employees directly or indirectly related to production process. Therefore such accounts should be chosen. Variety of expenditure of labour accounting data would reveal extra information that would grant a possibility to evaluate dynamics of different kind expenditure of labour, calculate amount of a single employee different kind expenditure of labour and compare the received value to the work results achieved by the employee, estimate influence of expenditure of labour change over company activity figures. Expenditure of labour control and accounting questions are little investigated in literature. Mostly attention is paid to whether the company calculates labour payment and reflects it in finance accountability in a correct manner. In order to have the control effectively influence company activity labour payment control limits should be extended including other type of expenditure of labour and adding extra procedures. “Expenditure of labour control form” is recommended for expenditure of labour control. Expenditure of labour control on the basis of recommended form results would give information whether expenditure of labour appear within the laws of Lithuanian Republic, Government resolutions and other law statements or there was no overpay case and calculated and paid out sums reflect in an accountancy of appropriate period.